The History of Tirana as an Important Factor in the Social and Cultural Developments Throughout the 20th Century - Xhaferri, Manjola (Mediterranean Journal of Social Sciences, 2012)
This paper aims at giving some very important social and cultural aspects, which were seen during the beginning of the 20thcentury, especially during the transformation of Tirana as the capital of Albania in February 1920. What is seen as most important in thispaper is, the political systems of Albania especially after the acknowledgment of Albania as an indipendent country in the internationalarena and the social and cultural effects it brought in the social life. The most important aspects that will be treated in this paper are asfollows:a. The history of Tirana and various of its legendsb. The political transformations during the 20th Century and their influence in the social lifec. Population’s movements, Tirana as part of this movementd. The new comers in front of a new mentality, imposed by the area where they settled down.These are some of the main issues the albanian society faces in general and especially the inhabitants of Tirana, whose integrity ismostly affected by the economical, social and cultural aspects of the metropolitan capital, Tirana. In this paper, we will take intoconsideration as well the changes the albanians had to confront after the 1990. We are mentioning here those citizens who left the city tolive in the country, making here a comparison of the both situations, of the previous and later life they had. Despite the clash of mentality,lets hope to see a cohabitation and an adaptionin of ideas and integrity of inhabitants of Tirana and other big cities of Albania in a nondistant future.